Breakups and Betrayals in Emerging Adulthood: A Developmental Perspective of Relationship Dissolution and Infidelity - Norona, Jerika C. (2018)
This dissertation includes two studies that focus on romantic experiences in emerging adulthood (ages 18-25), romantic dissolution (Study 1) and extradyadic intimacy (Study 2), and their relationship with developmental and individual factors. Each study uses two unique community samples of emerging adults who have attended college as well as those who have not attended college in the past. Importantly, both studies examine romantic dissolution and extradyadic intimacy from a developmental perspective, taking into account the salient developmental tasks of independence and interdependence faced by young people. Additionally, individual factors, including perceptions of emerging adulthood (Study 1), attachment style (Study 2), and gender (Studies 1 and 2) are examined as they relate to emerging adults' pursuit of these romantic experiences. Each study concludes with implications for relationship education for emerging adults